(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
Introduction: Tumor lysis syndrome (TLS) is a common complication of malignancies and can result in renal failure or death. Review: In paediatric tumor with a high proliferative rate and relatively large mass and a high sensitivity to cytotoxic agents, beging of therapy often results in the rapid release of intracellular metabolic products of proteins and nucleic acids into the bloodstream. Raised concentrations of uric acid, phosphates, potassium and urea can overwhelm the body’s homeostatic mechanisms to excrete these materials and result in the clinical spectrum associated with TLS. Clinical features include gastrointestinal disturbances, neuromuscular effects, cardiovascular complications, acute renal failure and death. The incidence of clinical TLS is approximately 6% for acute leukemias and 10% for lymphomas. Pediatric cancers are the leading cause of death by disease in children. The most common pediatric cancers include the leukemias, lymphoma, Wilms’ tumor and neuroblastoma. Thus, TLS prevention and treatment is a multidisciplinary approach involving the collaboration of medical oncologists/ hematologists and nephrologists has role for optimal patient outcomes. Rehydration is fundamental in the management of TLS. For hyperuricemia we may use allopurinol. Conclusion: The early diagnosis and treatment of metabolic abnormalities prevents the severe complications of tumor lysis syndrome. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 55-60